The Revival of an Old Assailant with Oral Implications (Indian Journal of Case Reports, 2017)
Syphilis is among the primogenital documented sexually transmitted diseases (STD). In the past decade, its incidence has levitated significantly in the urbanized world. Oral syphilitic lesions, the most common extragenital insignia of infection, pose a diagnostic challenge to dentists, who are frequently the first to observe them. Oral lesions in secondary stage syphilis are particularly common in association with general symptoms and cutaneous eruptions. However, an exclusive oral localization, not associated with general manifestations, is uncommon. We report a case of a 19-year-old male patient with isolated oral ulceration as the sole presentation of secondary syphilis.